The Big Book of X-Bombers & X-Fighters : USAF Jet-Powered Experimental Aircraft and Their Propulsive Systems /: USAF Jet-Powered Experimental Aircraft and Their Propulsive Systems. (2016) - Pace, Steve
No abstract available